Integration of multiple climate models to predict range shifts and identify management priorities of the endangered Taxus wallichiana in the Himalaya–Hengduan Mountain region - Li, Peixian; Zhu, Wenquan; Xie, Zhiying; Qiao, Kun (Journal of forestry research, 2020)
Taxus wallichiana Zucc. (Himalayan yew) is subject to international and national conservation measures because of its over-exploitation and decline over the last 30 years. Predicting the impact of climate change on T. wallichiana ’s distribution might help protect the wild populations and plan effective ex situ measures or cultivate successfully. Considering the complexity of climates and the uncertainty inherent in climate modeling for mountainous regions, we integrated three Representative Concentration Pathways (RCPs) (i.e., RCP2.6, RCP4.5, RCP8.5) based on datasets from 14 Global Climate Models of Coupled Model Intercomparison Project, Phase 5 to: (1) predict the potential distribution of T. wallichiana under recent past (1960–1990, hereafter “current”) and future (2050s and 2070s) scenarios with the species distribution model MaxEnt.; and (2) quantify the climatic factors influencing the distribution. In respond to the future warming climate scenarios, (1) highly suitable areas for T. wallichiana would decrease by 31–55% at a rate of 3–7%/10a; (2) moderately suitable areas would decrease by 20–30% at a rate of 2–4%/10a; (3) the average elevation of potential suitable sites for T. wallichiana would shift up-slope by 390 m (15%) to 948 m (36%) at a rate of 42–100 m/10a. Average annual temperature (contribution rate ca. 61%), isothermality and temperature seasonality (20%), and annual precipitation (17%) were the main climatic variables affecting T. wallichiana habitats. Prior protected areas and suitable planting areas must be delimited from the future potential distributions, especially the intersection areas at different suitability levels. It is helpful to promote the sustainable utilization of this precious resource by prohibiting exploitation and ex situ restoring wild resources, as well as artificially planting considering climate suitability.